Seasonal variations in microplastic distribution on Macau’s windward and leeward beaches: weak spatial autocorrelation - Zong, Changxing; Jabeen, Khalida; Zhu, Lixin (Frontiers in Marine Science, 2025)
Beaches have been recognized as hotspots of microplastic (MP) pollution, posing an emerging threat to both environment and human health. Understanding the sources and key factors influencing MP distribution on beaches is crucial for developing effective management strategies. Here, MPs in two major tourism beaches with different orientations in Macau were seasonally investigated for the first time. The average abundance of MPs on Macau beaches was 36.56 ± 38.05 n/kg in spring and 628.63 ± 1462.31 n/kg in autumn, with foam accounting for over 85% of the total MPs in both seasons. The spatial autocorrelation of MP distribution across both seasons and beaches was weak, with no significant patterns of spatial clustering or dispersion observed.The abundance of MPs was significantly higher in autumn than in spring, mainly due to the large amount of polystyrene foam brought by the tides from the sea. It was also noticed that the abundance of MPs on windward beaches was significantly higher than that on leeward beaches, highlighting the important role of wind in dominating the MPs on coastal beaches in the studied region. The chemical composition of MPs, analyzed using Fourier-transform infrared (FTIR) spectroscopy, revealed that most MPs originated from nearby areas. The findings will provide scientific insights for policy development aimed at mitigating plastic pollution in densely populated regions.